Trace element determination of Argentine wines using ETAAS and USN-ICP-OES - Lara, Rodolfo Francisco (2005)
The objective of this work was to develop a method to determine the metal content in wine samples from the province of Mendoza in Argentina. Ten samples of white wine and 10 samples of red wine available in the supermarket were analyzed for the metals aluminium, cadmium, calcium, chromium, copper, iron, nickel, lead and zinc by electrothermal atomic spectrometry (ETAAS) and ultrasonic nebulization was coupled to inductively coupled plasma optical emission spectrometry (USN-ICP-OES). The aluminium, cadmium, calcium, copper, iron, lead, zinc, chromium concentrations were between 17.0-18.0 μg l -1, 1.0-4.7 μg l -1, 10.0-15.0 mg l -1, 23.0-28.0 μg l -1, 480-790 μg l -1, 50-90 μg l -1, 24-130 μg l -1, and <0.2-6.25 μg l -1, respectively. The levels compare well with those reported for similar wines from some other parts of the world. A significant aspect in this paper is the samples mineralization step, which allowed the direct determination of the metals. Concerning to the Cd determination, a refluxing digestion system was used for the pretreatment of the samples.